Formas de regulação dos programas de integridade no Brasil - Matos, Amanda Prado de (2019)
This thesis presents the different approach made by the State for regulating compliance programs in Brazil, considering the national and international historical context of the movement against corruption. This thesis will analyze the corporate compliance policies of which compliance programs are part with focus in the structural elements of an effective compliance program and the benefits of its implementation in the company. At the end this thesis presents the enforced self-regulation as the model used by the State against corruption and it organizes the regulations in three groups: recommendations, requirements and mandatory regulation, including the characteristics the norms of such groups